Improved Short-Circuit Current Calculation of Doubly Fed Wind Turbines With Uninterrupted Excitation - Yin, Jun (Frontiers in Energy Research, 2021)
With the enlarging scale of doubly-fed induction generator (DFIG) connected to power system, the influence of short-circuit current to system relay protection couldn’t be ignored. Setting and configuration of relay protection would be affected by imprecise short-circuit current calculation. However, existing studies only consider the situation that Crowbar is input and rotor excitation is blocked. China's new network standard requires the DFIG output reactive support current, it will change the characteristics of short-circuit current. To solve this problem, on the basis of analyzing the characters of DFIG's transient equal-potential, the transient model of DFIG with uninterrupted excitation is provided. Base on the characteristics of non-abrupt change of flux linkage and the requirement of new grid standard reactive support current, the calculation method of DFIG short-circuit current with uninterrupted excitation is put forward. Based on RTDS, the digital-analog experimental platform containing the actual control unit of DFIG converter is founded, the proposed short-circuit current RMS value calculating method is validated.